Gender stereotypes of changing of life perspectives and strategies of a person in crisis situations - Volodarska, Nataly (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article describes psychological basis of changing life perspectives of individual in crisis situation and methods of their correction. The methodological foundations of impact of changing life strategies of personality that corrects changes in life perspectives are considered. There is presented an analysis of the latest research of individual’s problems of rehabilitation in crisis situations. A comparative analysis of personal changes of life perspectives for women and men was performed. The differences in changes in life perspectives of women and men in crisis situations are revealed. There were established features of impact of crisis situations on building new goals and strategies to achieve them. The specificity of changes of life strategies of family members after being in ATO z one were characterized. Marked differences in the most significant themes of changing of life perspectives of men and women are displayed in diagrams. Description of each themes of life perspectives were given. There were selected methods of influence on a process of life perspectives harmonization, plans and values of a person that was in life crisis situations. There were marked directions of a group and individual work with young families that were in a rehabilitation centre. Methods of work with men and women to restore the time-spatial orientation of past, present and future were identified and tested. There was developed a model of development of person’s life strategies which activated construction of new perspectives in process of self-determination of person’s development.